The Poetics of Participation: The Organizing of Participation in Contemporary Art - Ditte Vilstrup Holm (Copenhagen Business School (CBS), 2019)
This thesis engages with the organizing of participation in participatory art that constitutes the so-called social turn in contemporary visual art. The purpose of the research project is to generate new knowledge about participatory art, in particular, by investigating the organizational processes involved in these practices. To this end, an in-depth, qualitative case study of the organizing of participation for a public work of art was conducted. Using sociologist John Law's notion of modes of ordering as a tool to sharpen an analysis of the patterning effects discerned from fieldwork observations, the thesis argues that the organizing of participation in contemporary art is an effect of four main interacting modes of ordering, termed artistic autonomy, administration, the site, and public interest. First, the thesis respectively explores the modes of ordering as singular ordering patterns in the networks of the social, and then describes how they interact and the effects of that interaction in the case study. The thesis thus contributes to a new `organizational turn' in art theory that considers the way in which artistic practices are concerned with the organizing and reorganizing of social ordering processes, while themselves being embedded within and filtered into other organizing practices. The thesis also contributes to organization studies' interest in the relationship between art, aesthetics, and processes of organizing, suggesting that contemporary art theory and organization studies both ponder the question of how artistic practices generate new forms of organizing that counter society's prevailing economic rationale.
hdl:10398/9711
Keywords: 650